PENELITIAN KETERSEDIAAN AIR IRIGASI DI KOTA PAYAKUMBUH DALAM RANGKA PENINGKATAN PRODUKSI PADI - Marfini Barmawi (JURNAL SUMBER DAYA AIR, 2007)
Payakumbuh a small town with a self government is the capital of Kabupaten Limapuluh Kota - WestSumatera. About 60 % of the land area is being used for agriculture and consequently water demand is veryhigh. With the growth of population and its social and economic condition, the reguirement for water has alsoincreased.In anticipating the problem, concern is be given to the development and management of water resources.Particulary to the two water sources passing the region, i.e. the Batang Agam and Batang Lampasi. A weircan be developed in the Batang Agam at Padang Ambacang, whereas river storage structures can bedeveloped, such as dams, long storages and water wheels, in the Batang Lampasi. In addition to developingthe water system, paddy production can be inereased by applying the System of Rice Intensification (SRI).